2021
DOI: 10.3390/nu13061999
|View full text |Cite
|
Sign up to set email alerts
|

Lipoic Acid Exacerbates Oxidative Stress and Lipid Accumulation in the Liver of Wistar Rats Fed a Hypercaloric Choline-Deficient Diet

Abstract: Non-alcoholic fatty liver disease (NAFLD) is currently estimated as the most prevalent chronic liver disease in all age groups. An increasing body of evidence obtained in experimental and clinical data indicates that oxidative stress is the most important pathogenic factor in the development of NAFLD. The study aimed to investigate the impact of α-lipoic acid (LA), widely used as an antioxidant, on the effects of a hypercaloric choline-deficient diet. Male Wistar rats were divided into three groups: control di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Several studies evidence a positive systemic ALA role in promoting antioxidant activity. For instance, a dose of 600 mg/day ALA increased plasma SOD activity in diabetic patients [44] as well as rats fed a hypercaloric choline-deficient diet showed a significant increase in plasma SOD after receiving ALA [45]. Moreover, ALA supplementation restored the transcription of gene encoding SOD which was decreased by HFD in mice plasma [46].…”
Section: Discussionmentioning
confidence: 98%
“…Several studies evidence a positive systemic ALA role in promoting antioxidant activity. For instance, a dose of 600 mg/day ALA increased plasma SOD activity in diabetic patients [44] as well as rats fed a hypercaloric choline-deficient diet showed a significant increase in plasma SOD after receiving ALA [45]. Moreover, ALA supplementation restored the transcription of gene encoding SOD which was decreased by HFD in mice plasma [46].…”
Section: Discussionmentioning
confidence: 98%
“…As has been repeatedly shown in clinical observations, deficiency of this vitamin is an important etiological factor in the development of non-alcoholic fatty liver disease [41] and metabolic syndrome [42]; in particular, the latter is reflected in the growth of LDL cholesterol levels in agreement with our observations (see Figure 5c). Deficiency of vitamin B 12 [43] and lipoic acid [44,45] can also disturb lipid metabolism and lead to excess fat accumulation in the liver; this is considered the initial study of steatohepatitis. The accumulation of fat in the liver, most noticeable at the highest dose of BNC in group 4, could have a negative impact on hepatic metabolic function in terms of the transformation of nitrogenous compounds, as reflected by an increase in creatinine levels and a decrease in uric acid in the blood serum; the latter could also result in a decrease in blood antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…The antilipidemic effect observed in this study and inhibition of α-amylase reported previously [19] explain the significant improvement in OGTT by geraniin and GEE. TG overload in the pancreas has been demonstrated to disrupt β-cell function [33] and induce oxidative stress (OS) [34]. Hence, reduction in TG appears to have also improved glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%